Preterm Complete Uterine Rupture With En Caul Expulsion - Stanley Eboh; Suna Burghul; Michael Galloway; Asley Sanchez; Gary Ventolini (Clinical Medicine Insights: Case Reports, 2022)
Spontaneous uterine rupture is a catastrophic obstetric complication for both the mother and fetus. We highlight a case of a 32-year-old G2P1A0L1 Hispanic female at 36 weeks gestation who presented to the labor and delivery unit with minimal prenatal care, complaining of abdominal pains and vaginal bleeding. An abdominopelvic ultrasound confirmed an empty uterus and fetal demise in the abdominal cavity, leading to an exploratory laparotomy to evacuate the fetus. At surgery, a preterm sized fetus “en caul” with intact amnions was floating in the abdominal cavity and a hemostatic, complete rupture of the anterior uterine wall was discovered. Uterus was repaired and the patient recovered postoperatively without complications. Despite the best evidence suggesting that a history of low-transverse Cesarean section poses a low risk for spontaneous uterine rupture, this complication should always be considered and patients should be counseled regardless of the low risk should they desire a cesarean section.